2019
DOI: 10.1371/journal.pone.0224171
|View full text |Cite
|
Sign up to set email alerts
|

A participatory community case study of periurban coastal flood vulnerability in southern Ecuador

Abstract: BackgroundPopulations in coastal cities are exposed to increasing risk of flooding, resulting in rising damages to health and assets. Adaptation measures, such as early warning systems for floods (EWSFs), have the potential to reduce the risk and impact of flood events when tailored to reflect the local social-ecological context and needs. Community perceptions and experiences play a critical role in risk management, since perceptions influence people’s behaviors in response to EWSFs and other interventions.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…The increasing practice of building on watercourses and wetlands, indiscriminate dumping and silting of drains has exacerbated the perennial urban floods in Limbe. This result confirms the findings of [46,47] who highlighted that increase incidence of floods is because of the low-lying nature of the land, high rainfall intensity and duration, deposition of sediments in storm drains Field results show that 31.4% of households in Down Beach are not aware of flood risk zones as compared to only 14.6% in Cassava Farm. Poor knowledge of flood risk zones can result in the construction of houses in zones that are prone to floods.…”
Section: Perceived Causes Of Flood Disastersupporting
confidence: 90%
“…The increasing practice of building on watercourses and wetlands, indiscriminate dumping and silting of drains has exacerbated the perennial urban floods in Limbe. This result confirms the findings of [46,47] who highlighted that increase incidence of floods is because of the low-lying nature of the land, high rainfall intensity and duration, deposition of sediments in storm drains Field results show that 31.4% of households in Down Beach are not aware of flood risk zones as compared to only 14.6% in Cassava Farm. Poor knowledge of flood risk zones can result in the construction of houses in zones that are prone to floods.…”
Section: Perceived Causes Of Flood Disastersupporting
confidence: 90%
“…As a result of their exposure to flooding, they had to live in unsafe conditions that adversely affected their livelihood and living conditions. As observed by Tauzer et al (2019), sensitive populations are most likely to suffer from increased risk of infectious diseases caused by mobility limitations and lower immunity levels. Low-wage income earners were also perceived to be socially vulnerable because of limited opportunities for labor during disasters.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 We used Bayesian hierarchical models of monthly cases of dengue between 2002 and 2014 (Figure S1A) and malaria between 1990 and 2015 (Figure S1B) for the city of Machala, in southern Ecuador, a city at risk of the health impacts of climate change. 15 Prior studies found that dengue and malaria transmission were sensitive to changes in climate in this region. 12,13 We compared five global products of monthly mean temperature and precipitation, with local weather station data, to investigate the impact of local climate variation on these two vector-borne diseases.…”
Section: Implications Of Different Climate Data Sources On Understanding Vector-borne Diseases In Southern Ecuadormentioning
confidence: 97%